Tema . Tema . Theme . Тема - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Roads and highways in Russia today. Featured in the program: Fedorov, Vladimir Aleksandrovich (Head of the Main Directorate of the State Traffic Safety Inspectorate of the Ministry of Internal Affairs of Russia) Contributors: List'ev, Vladislav Nikolayevich (Anchor) Series description: One of the first talk shows on Russian television. The program was produced by TV-company VID and broadcasted on the First Channel "Ostankino" from January 31, 1992. Initially, the program was hosted by Vladislav Listiev. Передача об автомобилях и дорогах. В программе участвуют: Федоров, Владимир Александрович (Начальник Главного управления ГИБДД МВД России) Создатели: Листьев, Владислав Николаевич (Ведущий/Ведущая) Описание серии: Одно из первых российских ток-шоу. Передача производилась телекомпанией ВИД и выходила в эфир на 1-м канале Останкино с 31 января 1992 года. Первоначально программу вел Владислав Листьев.